2004
DOI: 10.1007/s00436-004-1145-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombination does not generate pinworm susceptibility during experimental crosses between two mouse subspecies

Abstract: The susceptibility to Aspiculuris tetraptera of European Mus musculus hybrids is thought to reflect the disruption of genomic co-adaptation through recombination of the parental genomes. Here, we compared the susceptibility to this parasite between parents and experimental hybrids (intersubspecific until F4, intrasubspecific F1, F2) to clarify the contributions of heterosis and subspecies incompatibility. F1 showed hybrid vigor. Unlike intrasubspecific F2, intersubspecific F2 were less resistant than F1, but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In all cases, we find significant taxon differences. Our results are consistent with experimental infection of domesticus and musculus mouse strains and their hybrids (from F1 to F4) in controlled conditions with the pinworm A. tetraptera (Derothe et al 2004), which showed either significantly reduced load (F1, F3, F4) or no significant effect (F2).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In all cases, we find significant taxon differences. Our results are consistent with experimental infection of domesticus and musculus mouse strains and their hybrids (from F1 to F4) in controlled conditions with the pinworm A. tetraptera (Derothe et al 2004), which showed either significantly reduced load (F1, F3, F4) or no significant effect (F2).…”
Section: Discussionsupporting
confidence: 89%
“…Returning to the first of these three issues: we have suggested coadaption among immune genes is unlikely if they are using recombination to run a Red Queen race against parasites. Even if recombination is not breaking up coadapted gene complexes (Derothe et al 2004), there is still reason to expect hybridization to produce suboptimal genotypes. This is because hybridization involves admixture of alleles that have never coexisted in the same population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results illustrate the importance of using a combination of studies of natural populations and laboratory studies in constructing a model of speciation. More detailed studies of the hybrid genomes, including denser sampling of the genome in a greater number of hybrid mice, will help illuminate the specific mode of selection acting to create isolation between these taxa and complementary studies on fitness and behavior of mice from the hybrid zone, such as studies of hybrid sterility (Forejt and Ivanyi 1975; Storchova et al 2004; Britton‐Davidian et al 2005; Vyskocilova et al 2005; Good et al 2008a,b), mate choice preference (Laukaitis et al 1997; Talley et al 2001; Smadja and Ganem 2002; Smadja et al 2004; Bimova et al 2005), and susceptibility to parasites (Sage et al 1986a; Moulia et al 1993; Derothe et al 2001; Derothe et al 2004), may help link specific phenotypes to the patterns of introgression documented here.…”
Section: Discussionmentioning
confidence: 99%
“…Infection experiments using the protozoan Sarcocystis muris led to a similar conclusion (Derothe, Le Brun, Loubes, Perriat‐Sanguinet, & Moulia, ). Other laboratory experiments, however, showed either no effect in inter‐subspecies F1s on helminth load or even reduced load in inter‐subspecies F1s compared to pure mouse strains (Derothe, Porcherie, Perriat‐Sanguinet, Loubès, & Moulia, ; Moulia, Le Brun, Loubes, Marin, & Renaud, ). In 2012, more than two decades after the original field studies (Moulia et al, ; Sage et al, ), Baird et al found (with much larger sample size, clearer sampling design and more up to date inference) reduced helminth loads in hybrid mice (Baird et al, ), especially for the pinworms Aspiculuris tetraptera and Syphacia obvelata and the whipworm Trichuris muris .…”
Section: Introductionmentioning
confidence: 94%